Will the last be first and the first last? The role of classroom registers in cognitive skill acquisition. - Francesca Borgonovi; Maciej Jakubowski; Artur Pokropek (PLoS ONE, 2018)
The paper estimates the effect of students' position in the classroom register on their academic performance. We use a unique dataset from Poland which contains information on the academic outcomes of students in the humanities, science and mathematics lower secondary school exams as well as the position students occupy in their classroom register. We find that students whose names are recorded near the end of the class list have lower performance than those students whose names are recorded near the beginning of the list. The effect appears to be larger for performance in the humanities exam, and for low-achieving boys who attend large classes.